Measuring Competitiveness : Trade in Goods or Tasks? - Bayoumi, Tamim (IMF Working Papers; Working Paper ;, 2013)
With global supply chains, any value added or production task can be traded as part of goods. This means that competitiveness can be measured either in terms of 'tasks' (Bems and Johnson, 2012), or goods, but with goods prices reflecting the cost of tasks embedded in those goods. We show that when measuring competitiveness in goods, the formula used in computing the real effective exchange rates at the IMF (Bayoumi, Lee, and Jayanthi, 2005) needs to be expressed in terms of the price of value added and needs an additional term, which captures a gain or loss in competitiveness of goods due to outsourcing.